Multiple Antitumor Molecular Mechanisms Are Activated by a Fully Synthetic and Stabilized Pharmaceutical Product Delivering the Active Compound Sulforaphane (SFX-01) in Preclinical Model of Human Glioblastoma - Alessandro Colapietro (MDPI AG, 2021)
Frequent relapses and therapeutic resistance make the management of glioblastoma (GBM, grade IV glioma), extremely difficult. Therefore, it is necessary to develop new pharmacological compounds to be used as a single treatment or in combination with current therapies in order to improve their effectiveness and reduce cytotoxicity for non-tumor cells. SFX-01 is a fully synthetic and stabilized pharmaceutical product containing the α-cyclodextrin that delivers the active compound 1-isothiocyanato-4-methyl-sulfinylbutane (SFN) and maintains biological activities of SFN. In this study, we verified whether SFX-01 was active in GBM preclinical models. Our data demonstrate that SFX-01 reduced cell proliferation and increased cell death in GBM cell lines and patient-derived glioma initiating cells (GICs) with a stem cell phenotype. The antiproliferative effects of SFX-01 were associated with a reduction in the stemness of GICs and reversion of neural-to-mesenchymal trans-differentiation (PMT) closely related to epithelial-to-mesenchymal trans-differentiation (EMT) of epithelial tumors. Commonly, PMT reversion decreases the invasive capacity of tumor cells and increases the sensitivity to pharmacological and instrumental therapies. SFX-01 induced caspase-dependent apoptosis, through both mitochondrion-mediated intrinsic and death-receptor-associated extrinsic pathways. Here, we demonstrate the involvement of reactive oxygen species (ROS) through mediating the reduction in the activity of essential molecular pathways, such as PI3K/Akt/mTOR, ERK, and STAT-3. SFX-01 also reduced the in vivo tumor growth of subcutaneous xenografts and increased the disease-free survival (DFS) and overall survival (OS), when tested in orthotopic intracranial GBM models. These effects were associated with reduced expression of HIF1α which, in turn, down-regulates neo-angiogenesis. So, SFX-01 may have potent anti-glioma effects, regulating important aspects of the biology of this neoplasia, such as hypoxia, stemness, and EMT reversion, which are commonly activated in this neoplasia and are responsible for therapeutic resistance and glioma recurrence. SFX-01 deserves to be considered as an emerging anticancer agent for the treatment of GBM. The possible radio- and chemo sensitization potential of SFX-01 should also be evaluated in further preclinical and clinical studies.